EFEKTIVITAS PEMBELAJARAN SAINS MENGGUNAKAN STORYBOOK DIGITAL BERBASIS AUGMENTED REALITY DALAM KEMAMPUAN BERPIKIR KRITIS SISWA SD - Aurel Abelita Elsa Suroso; Cholifah Tur Rosidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the differences in students' critical thinking skills in science learning between those using digital storybooks and those not using AR-based digital storybooks. This type iof iresearch iis iquantitative iwith ian iexperimental method using a quasi-experimental design with a Posttest-only control group design, in which both groups are not given a pretest, but only a posttest after the treatment. The results of this study show a significant increase in the critical thinking skills of fifth-grade students in science learning. The average posttest score in the control class was 84, and after applying tthe AR-based digital storybook, The average post-test score in the experimental class increased to 91. thus, this AR- based digital storybook improved students' critical thinking outcomes in science learning after implementing the AR-based digital storybook.